Transgenic Rice Plants Expressing Artificial miRNA Targeting the Rice Stripe Virus MP Gene Are Highly Resistant to the Virus - Liya Zhou; Quan Yuan; Xuhong Ai; Jianping Chen; Yuwen Lu; Fei Yan (Biology, 2022)
Rice stripe virus (RSV) causes one of the most serious viral diseases of rice. RNA interference is one of the most efficient ways to control viral disease. In this study, we constructed an amiRNA targeting the RSV MP gene (amiR MP) based on the backbone sequence of the osa-MIR528 precursor, and obtained marker-free transgenic rice plants constitutively expressing amiR MP by Agrobacterium tumefaciens-mediated transformation. A transient expression assay demonstrated that dimeric amiR MP could be effectively recognized and cleaved at the target MP gene in plants. Northern blot of miRNA indicated that amiR MP-mediated viral resistance could be stably inherited. The transgenic rice plants were highly resistant to RSV (73–90%). Our research provides novel rice germplasm for RSV control.